EFEKTIVITAS CITES ( CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA) DALAM MENGATUR PERDAGANGAN HIU DI KAWASAN CORAL TRIANGEL ( IMPLEMENTASI DI INDONESIA) - Ollani Vabiola Bangun; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describes effectiveness regulation of CITES ( Convention on InternationalTrade In Endangered Species of Wild Fauna and Flora) while regulate shark trade in CoralTriangel ( implementation in Indonesia). Its existence are threatened by illegal trade and illegalfishing. Sharks are particularly vulnerable to over-exploitation due to their biologicalcharacteristics of maturing late, having few young and being long-lived. According to FAO data,Indonesia is the major shark catching country in the world. Most parts of the sharks are utilized(fin, skin, meat, bones, stomach, liver, teeth) and generally sold through brokers/ traders atauction for domestic sale or export.This research is a descriptive-explanation research. It uses thelibrary research method with that collecting secondary data from books, journals, and internet. Ituses international regime theory and effectivenes regime to explain implementation Indonesia toregulate shark trade. This result of this research shows Indonesian was ineffective on regulateimplementation CITES because illegal trade and illegal fishing still happens, over exploitationand the minimum protection of status and regulation about shark in Indonesia.Keyword : CITES, illegal trade, illegal fishing, over-exploitation